Studi Etnografi Persepsi Label Halal terhadap Keputusan Konsumen: Studi Kasus Masyarakat Muslim Bali - Hafifah, Nur; Abrori, Faizul; Rinawati; Mustaqim Makki (ARBITRASE: Journal of Economics and Accounting, 2025)
Indonesia, as the country with the largest Muslim population in the world, places great importance on the need for halal products, particularly in food and beverage consumption. The halal label is now seen not only as a religious requirement but also as a symbol of trust, quality, and cleanliness. However, in minority Muslim communities such as in Candikuning Village, Bedugul, Bali, challenges arise in ensuring the halalness of daily consumption amidst the dominance of non-Muslim business operators. This study aims to understand how the Muslim community in Candikuning Village interprets the halal label, both in its formal form (MUI certification) and symbolic form (Islamic identity of food stalls), and how these perceptions influence their consumption decisions. This research uses a qualitative approach with ethnographic methods. An ethnographic approach is used to explore the meaning behind halal consumption practices within the local socio-cultural context. The findings are expected to contribute conceptually to the study of Muslim consumer behavior and serve as a foundation for business actors and certification bodies in formulating more contextual and inclusive halal labeling and education strategies, particularly in multicultural regions such as Bali. This research employs a qualitative approach with ethnographic methods to explore perceptions of the halal label in the consumption practices of the Muslim minority in Candikuning Village, Bali. The results show that the Muslim community in Candikuning interprets the halal label not only as a religious requirement but also as a symbol of trust, cleanliness, and moral responsibility. Both official halal labels and informal Islamic symbols are used as consumption guidelines, reflecting religious awareness and caution in a multicultural environment.